A Cost‐Effective, Aqueous‐Solution‐Processed Cathode Interlayer Based on Organosilica Nanodots for Highly Efficient and Stable Organic Solar Cells. Issue 38 (13th August 2020) - Cui, Mengqi; Li, Dan; Du, Xiaoyan; Li, Na; Rong, Qikun; Li, Ning; Shui, Lingling; Zhou, Guofu; Wang, Xinghua; Brabec, Christoph J.; Nian, Li
Abstract: The performance and industrial viability of organic photovoltaics are strongly influenced by the functionality and stability of interface layers. Many of the interface materials most commonly used in the lab are limited in their operational stability or their materials cost and are frequently not transferred toward large‐scale production and industrial applications. In this work, an advanced aqueous‐solution‐processed cathode interface layer is demonstrated based on cost‐effective organosilica nanodots (OSiNDs) synthesized via a simple one‐step hydrothermal reaction. Compared to the interface layers optimized for inverted organic solar cells (i‐OSCs), the OSiNDs cathode interlayer shows improved charge carrier extraction and excellent operational stability for various model photoactive systems, achieving a remarkably high power conversion efficiency up to 17.15%. More importantly, the OSiNDs' interlayer is extremely stable under thermal stress or photoillumination (UV and AM 1.5G) and undergoes no photochemical reaction with the photoactive materials used. As a result, the operational stability of inverted OSCs under continuous 1 sun illumination (AM 1.5G, 100 mW cm −2 ) is significantly improved by replacing the commonly used ZnO interlayer with OSiND‐based interfaces. Abstract : An aqueous‐solution‐processed cathode interlayer based on cost‐effective organosilica nanodots (OSiNDs) is demonstrated for organic solar cells (OSCs) with power conversion efficiency over 17% and excellent operational stability. The high photostability of OSiNDs‐based OSCs is attributed to the avoidance of photoinduced shunts and the photocatalytic effect, which are ineluctable shortcomings in inverted OSCs based on ZnO cathode interlayers.